Single-Center Description of Therapeutic Anticoagulation Practices and Outcomes in Large Hemispheric Infarctions. Issue 6 (December 2022) - Breit, Hannah; Sterenstein, Andrea; Abburi, Nandini; Song, Sarah; John, Sayona; Da Silva, Ivan; Koffman, Lauren
Abstract : Background and Objectives: Large hemispheric infarctions (LHIs) are associated with significant morbidity and mortality, with limited data on therapeutic anticoagulation (AC) management. We provide a descriptive analysis of the type of therapeutic AC used, the timing of introduction, rate of of radiographic vs symptomatic hemorrhagic transformation (HT), and patient outcomes. Methods: This was a retrospective review of patients with acute ischemic stroke admitted to the Neurosciences intensive care unit at a tertiary care center from January 2012 to December 2018. Inclusion criteria included admission imaging with stroke size ≥ two-thirds of the middle cerebral artery territory, ± other vascular territory, and need for therapeutic AC. HT categories included hemorrhagic infarction types 1 and 2 and parenchymal hematoma types 1 and 2. The primary outcome included HT with and without an associated clinical change. Secondary outcomes included disposition at discharge and modified Rankin Scale (mRS) score at discharge and at follow-up when available. Results: A total of 2, 317 patients were screened, 380 met the inclusion criteria for LHI, and 105 received AC. The mean age was 64 years (SD 16.8), and 50% (n = 53) were female. The mean admission NIH Stroke Scale score was 20 (SD 5.9). The mean poststroke timing to initiation of AC was 17 days (SD 10.1) (median 14 [interquartile range 10–19 days]). Indications for AC included atrial fibrillation (51%), cardiac thrombus (19%), venous thromboembolism (19%), and other (10%). Heparin was most commonly used in the very early (≤7 days) group (n = 11, 79%), whereas vitamin K antagonists without a bridge were the most commonly used among the entire cohort (n = 54, 51%). Radiographic HT was seen in 68 patients (65%) before AC initiation. After initiation of AC, 70 patients had repeat imaging, with 6 cases (6%) of worsening radiographic HT and 4 cases (4%) of symptomatic deterioration, of which 3 required reversal of AC. At discharge, 7 patients (7%) had a good outcome (mRS score 0–2). Discussion: Although radiographic HT is common among patients with LHI, it does not always portend symptomatic clinical deterioration. Further research regarding AC timing and safety is necessary.